Assessing Speaking Skills in English Matriculation Classes: Challenges and Strategies - Nurma Atalsa Sofyansah; Siti Mafulah; Agus Sholeh; Maria Cholifah; Siti Mutmainnah (ETERNAL (English Teaching Journal), 2026)
This research revealed two main issues regarding speaking assessment, that is students’ low speaking confidence and low vocabulary mastery. These two issues hampered students in delivering their ideas fluently and do not speak well in the speaking assessment. To solve the problems, the researcher employed some strategies. This study aimed at describing the problems of the learners and the approaches used by the teacher in carrying out speaking tests in a matriculation class of MAN 1 Blitar. Qualitative descriptive approach with 34 students as subject, the data was collected by conducting class observation, conducting interview with English teacher and some students, and analysing students’ speaking performance tasks. The result showed that some students were reluctant to speak because of fear of making mistakes, lack of self-confidence, and lack of vocabulary. The teacher used three strategies which are providing vocabulary support, conducting group discussion, and providing formative feedback to help students in doing speaking assessments. The result showed that some students were reluctant to speak because of fear of making mistakes, lack of self-confidence, and lack of vocabulary. The teacher used three strategies which are providing vocabulary support, conducting group discussion, and providing formative feedback to help students in doing speaking assessments. This research reveals the students’ problems in speaking assessment and the teacher’s strategy in conducting speaking assessments in matriculation class. The teacher’s scaffolding strategy helps students in delivering ideas fluently and speaking well. The result demonstrates the importance of considering both effective and linguistic factors in conducting speaking assessment. The result might be used as the reference for English teacher to conduct better speaking assessment.